Properties of CrN thin films deposited in plasma-activated ABS by reactive magnetron sputtering - Pedrosa, Paulo Eduardo Teixeira Baptista (2018)
In this work, magnetron sputtered CrNx thin films with nitrogen concentrations ranging from 17 to 30 at.% were deposited on plasma activated ABS. Two sets of thin films were obtained by varying the N-2 flow inside the vacuum chamber (series #1) and the deposition time (series #2). The polymer samples were also subjected to plasma treatment in Ar prior to the CrNx thin films' deposition, in order to enhance the adhesion. The fundamental microstructural, chemical and physical properties, as well as the electrochemical and adhesion behavior of the CrNx thin films, were assessed by SEM, XRD, 3D profilometry, RAMAN, colorimetry, OCP measurements and cross-cut tape test. Main results show that high-quality CrNx films with a low percentage of defects were obtained. The CrNx film sputtered with 3 sccm N-2 for 20 min was considered to possess the most appropriate brightness, color, electrochemical stability and interfacial adhesion to fit the end-user requirements. Magnetron sputtering is thus a promising alternative to the hazardous chrome plating for an effective metallization of ABS.